Application of a composite membrane aerated biofilm with controllable biofilm thickness in nitrogen removal. Issue 3 (11th December 2019) - Zeng, Ming; Yang, Junfeng; Wang, Hongting; Wang, Chang; Wu, Nan; Zhang, Wu; Yang, Haowei
Abstract: BACKGROUND: The manipulation of aeration and biofilm thickness remain two key factors for membrane aerated biofilm. A composite membrane aerated biofilm (CMAB) reactor coated with microorganisms embedded in hydrogel was developed to quantitatively control the biofilm thickness by introducing the microbial immobilization technique. RESULTS: Results show that the thin gel film exhibited high dispersion coefficients of oxygen and substrates, and the crosslinking solution of sodium nitrate (NaNO3 ) contributed to the highest specific ammonium‐nitrogen (NH4 + ‐N) removal rate of 615.33 mg/(gVSS d) with respect to partial nitrification. Correspondingly, the microbial activity of this thin gel film was also the strongest. Therefore, with the simultaneous nitrification and denitrification, the gel thickness and air pressure co‐determined its efficiency. The optimum biofilm thickness and air pressure was 0.1 mm and 1 kPa, respectively, achieving the nitrogen removal rate of 1594.95 mg/(gVSS d). Furthermore, two abundant denitrifiers of Rhizobium and Thauera dominated the bacterial community of all four samples, and their proportion varied according to the aeration condition. Nitrosomonas tended to enrich in the thin CMAB under low air pressure and few Nitrospira existed. CONCLUSION: The thickness of developed CMAB can be quantitatively controlled, and the precise regulation of simultaneous nitrification and denitrification might be achieved by adjusting the gel film thickness and air pressure. The CMAB is supposed to greatly facilitate the application of membrane aerated biofilm for nitrogen removal. © 2019 Society of Chemical Industry